Pengkajian Phraseology (Bahasa) Pemanduan Lalu Lintas Penerbangan Makassar Advanced Air Traffic Services Di Bandara Internasional Sultan Hasanuddin-Makassar - Agustini, Endang Dwi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
ABSTRACTThis study hies to analyze the phraseology of the officer in Makassar Advenced Air Traffic Services (MAATS). The officers in MAATS consist of the officer of Aerodrome Control (ADC). Approach co11trol (APP). Area Control Center (ACC I, ACC II). They are expecting not nuzking any mistakes due to the language of pilotage airline traffic which caused by hasty speech and slip of the tongue since the difference of language dialect/ accent the foreigh pilots which come from many countries.The error in measuring the value contained in the region of 85% -95% may be norm control (tolerance) by the management by objective measurements of the work. Whereas in 2 (two) years in 2009 and 2010 never happened Breackdown of Separation (BOS) but in 2010 the ACC officers never happened Breackdown of Coordination (BOC) caused by weather and soon coordination through the equipment to the equipment connectivit CPDLC (Controller Pilot Data Link Communication) so that it can be confirmed. Key Words: phraseology (language) pilotage ADC, APP and ACC.